The effect of 5'-aminoimidazole-4-carboxamide ribonucleoside (AICAR) and 5'-aminoimidazole-4-carboxamide-ribonucleoside-phosphate (ZMP) on myocardial glucose uptake - Webster, Ingrid (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2005.